Korelasi Kualitas Tidur Dengan Fungsi Kognitif pada Tenaga Kesehatan Post Covid-19 di RSUDZA - Ika Marlia; Suherman, Suherman; Rachmawati, Cut Sri (Journal of Medical Science, 2024)
Long COVID is a condition when a COVID-19 survivor continues to experience symptoms of the disease for an extended period, even after having recovered from COVID-19, which is characterized by fatigue, neurocognitive impairment, muscle pain, weakness, and depression, which persist for more than 3-12 weeks after SARS-CoV-2 infection. Individuals infected with COVID-19 and healthcare workers on the front lines are at higher risk than others. Sleep quality parameters consist of quantitative aspects such as sleep duration and sleep latency, as well as subjective aspects such as deep sleep and rest. Some studies have reported that a decrease in sleep quality is closely related to an increased risk of cognitive decline. This study aims to determine the correlation between sleep quality and cognitive function in healthcare workers post-COVID-19 at RSUDZA. The research design used in this study is a cross-sectional. The subjects are healthcare workers at RSUDZA Banda Aceh who meet the inclusion criteria. The sample was selected using consecutive for assessing cognitive function using the MoCa-Ina and assessing sleep quality with PSQI. Data were analyzed using Spearman's correlation statistical test to examine the relationship between variables. There were 54 respondents, mostly female (79.6%). The MoCA-Ina score was >26 for 74.1% of respondents. Regarding the PSQI score in this study, most respondents (57.4%) had a score >5. The results of Spearman's correlation statistical test showed that there was no correlation between sleep quality and cognitive function in healthcare workers post-COVID-19 at RSUDZA.